Estudo em grupo como ferramenta pedagógica: uma pesquisa-ação da aprendizagem de química no ensino médio - Lima, Raimundo Plácido Melo Soares (2013)
The educational professional in the nowadays context has to meet some demands for acquiring more knowledge, nevertheless, the sort of knowledge that leads our students towards critical thinking and also towards a broadening of opportunities in order for their continuation of their learning and developing their ability to assimilate the ongoing technological changes. As a consequence, it is necessary to change the teacher himself in the environment of the classroom by means of new teaching methods for the students getting close to his methodology. In this context, this paper aims at having an analysis of the effectiveness of the method in the study of teamwork as a pedagogical tool for learning Chemistry in our high schools. We used a group of twelve students of the 3rd year of our high school system, which was divided into 4 smaller groups of 3 students each of them put together by affinity. The chosen subjects were: Properties of Matter; Substance and Mixture; Fractioning of Heterogeneous Mixtures and of Homogeneous Mixtures. The research took place within 7 meetings for its initial development, whereas the researcher used the presentation of these four aforementioned themes using different methodologies, individual study of the distributed educational materials, group discussion, clarification of doubts and application of assessment by means of summary essays. The groups used two meetings for the presentation of material developed by them without the assistance of the research teacher. New pieces of evaluation were also applied for comparison regarding the increase of learning how to learn and of learning how to do by the student themselves. At the very last meeting, we discussed together all the lessons which were presented by the students and they were given some suggestions on how to improve their assignments. The students developed some instructional materials to be used for the support of the many contents such as videos and games. The researcher made a comparison of the summary essays after the exposing of their group presentation not only to those students who had studied the contents as well as by students in the audience who demonstrated some progress in the absorption of the new knowledge through the summary essays which were prepared. And finally, the learning how to learn and learning how to do was effectively observed in the study of teamwork. The Educational Product which was prepared out of the prepared lessons and the developed teaching materials